PROTECTION OF INTELLECTUAL PROPERTY IN THE DIGITAL ENVIRONMENT OF INDUSTRY 4.0 IN THE CONDITIONS OF UKRAINE’S MILITARISM - Hordieieva, Inna (European Science, 2023)
The digitalization and development of Industry 4.0 are creating new challenges for intellectual property (IP) protection, such as unauthorized distribution of materials, data theft, and cyberattacks. In the context of martial law in Ukraine, these challen